Association between Histopathological Grading and Clinical Staging in Nasopharyngeal Carcinoma - Sonya M Naomi; Yussy A Dewi; Hasrayati Agustina (Journal of Medicine and Health, 2018)
Nasopharyngeal Carcinoma (NPC) is the most common cancer in head and neck. Grading of NPC is based on keratinization, growth, and cell junction, and it can be classified into well differentiated, moderately differentiated, poorly differentiated, and undifferentiated. On the other hand, the staging of NPC based on UICC/AJCC staging system is divided into Stage I-IVC. This classification is based on TNM that is related to the ability of cancer cells to invade normal cells. This study was conducted from May to June 2017 in Oncology Clinic of Otorhinolaryngology-Head and Neck Surgery Department and Pathology Anatomy Department of Hasan Sadikin General Hospital. This is an analytical correlative study with cross sectional design. The data is collected retrospectively from medical records of patients who are diagnosed as NPC with adequate grading and staging data. Incomplete medical records, multiple carcinoma, and recurrent carcinoma are excluded from this study. We find out that among 51 samples, predominant is Stage IVB NPC (37.3%) and undifferentiated grade NPC (76.5%). Statistical analysis shows that there is no significant association between grading and staging (r=0.275; p=0.159).This study concludes that there is no association between histopathological grading and clinical staging in nasopharyngeal carcinoma.Keywords: nasopharyngeal carcinoma, grading, staging